Biomechanical dynamic comparison of biodegradable pins and titanium screws for operative stabilization of displaced radial head fractures. (January 2020) - Wagner, Ferdinand C; Feucht, Matthias J; Konstantinidis, Lukas; Hohloch, Lisa; Yilmaz, Tayfun; Bernstein, Anke; Südkamp, Norbert P; Reising, Kilian
For radial head osteosynthesis, biodegradable implants are gaining in importance to minimize cartilage destruction and implant impingement and to supersede implant removal. Since loss of reduction and pseudarthrosis remain challenging complications, new implants should at least provide comparable biomechanical properties as commonly used metal implants. The objective of this study was to compare the treatment by polylactide pins to titanium screws and to quantify the produced cartilage defects. Eight pairs of human cadaver radii with a standardized Mason type II fracture were stabilized either by two 2.0-mm polylactide pins or titanium screws. The produced cartilage defects were quantified using an image analyzing software. Quasi-static loading was performed axially and transversally for 10 cycles each between 10 and 50 N. Afterward, implant loosening was tested by axial loading up to 10, 000 cycles, followed by load to failure testing. Polylactide pins showed less construct stiffness under axial (p = 0.017) and transversal (p = 0.012) loading, and one polylactide pins construct failed after two cycles of transversal loading. At axial loading, a high correlation between bone mineral density and construct stiffness was observed among polylactide pins (R = 0.667; p = 0.071), which was not seen among titanium screws (R = 0.262; p = 0.531). No difference in implant loosening was recorded after 10, 000 cycles (p = 0.237); however, one polylactide pins construct failed after 30 cycles and failure loads were higher for titanium screws (p=0.017). Polylactide pin produced smaller cartilage defects (p=0.012). In conclusion, simple radial head fractures treated by polylactide pins show less biomechanical stability than treated by titanium screws, particularly in osteoporotic bone which might lead to secondary loss of reduction. Due to smaller cartilage defects and equal properties under continuous loading, polylactide pins might represent a gentle alternative in patients with good bone quality making subsequent implant removal redundant.